Study on effect of pancreatic kininogenase on diabetic nephropathy-induced fibrosis via Notch1/Hes1/Pten/Akt signaling pathway - Mingjie Qing; Ximei Zhang; Qiangxiang Li; Canqun Yan (BMC Nephrology)
Abstract Objective To elucidate the mechanism by which pancreatic kininogenase (PKase) impacts renal fibrosis in diabetic nephropathy through modulation of the Notch1/Hes1 and Pten/Akt pathways. Methods This study employed in vivo models and cellular assays to investigate PKase’s effects on cellular viability, apoptosis, and oxidative stress. Assay kits were used to assess these parameters, while protein expression levels were measured via Western Blot and RT-qPCR. Histological changes in kidney tissues were analyzed using HE and Masson’s staining. Fibrosis markers—including E-cadherin, vimentin, α-SMA, Collagen I, TGF-β, and fibronectin—were evaluated through immunofluorescence and immunohistochemistry. Results After eight weeks of PKase treatment, significant improvements in blood glucose levels and associated symptoms were observed in diabetic nephropathy rats. Both in vivo and in vitro results demonstrated that PKase treatment inhibited the expression of diabetic nephropathy markers, including vimentin, α-SMA, FN, Collagen I, and TGF-β, while increasing the expression of E-cadherin. Additionally, the expression of Notch1, Hes1, and phosphorylated Akt (p-Akt) was upregulated, and Pten expression was suppressed, all of which were reversed by PKase treatment. Furthermore, both analyses indicated that PKase alleviated Jagged1-induced apoptosis and oxidative stress, and mitigated tubulointerstitial fibrosis. Conclusion PKase appears to ameliorate diabetic nephropathy-induced renal fibrosis by activating the Pten/Akt pathway and inhibiting the Notch1/Hes1 pathway, suggesting its potential as a therapeutic agent in diabetic nephropathy. Clinical Trial Number Not applicable.